Construção e validação do jogo interativo "sertão bom" sobre uso abusivo e problemático de drogas e o risco de suicídio - Viana, Lorenna Saraiva (2021)
Abusive and problematic drug use can decisively influence the mental health-illness process of users and their families. In this context, aspects related to suicide are also included, which, in turn, is characterized as the intentional act of an individual to extinguish his own life. It is also observed the emergence of the use of technologies as a potential tool to work on the various aspects of health, through playful and reflective methods. From this perspective, this study aimed to build and validate an interactive game for mobile devices, as an educational technology for the prevention of drug use and suicide. This is a study of technological development, developed in two stages: construction and validation, from September 2019 to March 2021. In the construction stage, university students from the Computer Engineering course took part. from the Federal University of Ceará (UFC), from the Computer Science course at UVA and from the Nursing course at the State University of Vale do Acaraú (UVA) and 02 professors, one from the Computer Engineering course at UFC and the other from the course of Nursing at UVA. In the validation stage, 15 mental health specialists and 3 (three) computer/informatics specialists participated. Workshops and systematic meetings mediated by the Contextualized Instructional Designer methodology were used to build the SerTão Bom game. For the second stage, the Content Validation Index (CVI) was used to validate the content and appearance with health experts mental and information technology, with data organization in Excel spreadsheets. The name of the game corresponding to “SerTão Bom” was defined. It is, therefore, a quiz-style game, with a total of 196 questions, available offline for the Android system, developed through the Unity program in 2D format. When starting the game, there is a roulette wheel, which addresses three main categories: Drugs, Suicide and Damage Reduction, which have questions related to each of them and which increase in complexity as the player progresses through the game. Regarding content validation, an overall CVI of 0.78 was obtained under the general characteristics; in organization IVC of 0.87 and writing style with IVC of 0.90. With regard to technical aspects, the game was validated with a CVI of 0.86 in the usability item; 0.88 for efficiency and functionality with an IVC of 1.00. In view of the construction and validation of the SerTão Bom interactive game, one can learn about the importance of developing mobile apps in the context of health education from the perspective that it aims to promote autonomy and co-responsibility of users with regard to its promotion process and health care.